Geochemical and acoustic evidence for the occurrence of methane in sediments of the Polish sector of the southern Baltic Sea - Aleksandra Brodecka; Piotr Majewski; Jerzy Bolałek; Zygmunt Klusek (Oceanologia, 2013)
This paper presents the results of geochemical and acoustic investigations of sediments in the Polish sector of the southern Baltic Sea. Its objective was toindicate areas of gas bubble formation and the occurrence of methane. Over 3000 nautical miles of transects were recorded using a variety of hydroacousticinstruments, and five coring points were selected for further analyses of pore waters(CH4, SO4-2, H2S, NH4+, total alkalinity) and sediments (grain size distribution,Corg, Ntot, LOI and WC). Gas turned out to be present at shallow depths in different forms such as recent and buried pockmarks, and gas-saturated sediments (including gas pockets and seepages). It was found that methane was widespread in the sediments of the study area, both in the surface sediments, e.g. in the vicinity of the Hel Peninsula or in the central Gulf of Gdańsk, and in deeper sediment layers, e.g. in the Gdańsk Deep and the Słupsk Furrow. Chemical analysis showed that as a result of the rapid decomposition of organic matter, sulphates were depleted in the top 20 cm layer of sediments and that methane was produced at relatively shallow depths (in some areas even at depths of 20-30 cm bsf) compared to other regions of the Baltic, reaching concentrations of >6 mmol l-1 in the 30-40 cm layer below the sediment surface. The sulphate-methane transition zone (SMTZ) was 4-37 cm thick and was situated in the uppermost 50 cm of the sediments.